2014
DOI: 10.1111/josh.12140
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of the Effectiveness of a Web‐Based Tailored Intervention Promoting Physical Activity in Adolescents: The HELENA Activ‐O‐Meter

Abstract: These findings should be taken into consideration when planning PA interventions in adolescents. Future intervention studies should also include moderation analysis in order to get a deeper understanding of why interventions are not effective for certain individuals and how this unresponsiveness could be overcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…As the short‐term health benefits of PA in adolescence are well documented, promoting PA in this age group is a relevant and pertinent research endeavor and a public health priority . The current data indicate the effective help that PBSPs can provide to adolescents to become cycling commuters.…”
Section: Implications For School Healthmentioning
confidence: 87%
“…As the short‐term health benefits of PA in adolescence are well documented, promoting PA in this age group is a relevant and pertinent research endeavor and a public health priority . The current data indicate the effective help that PBSPs can provide to adolescents to become cycling commuters.…”
Section: Implications For School Healthmentioning
confidence: 87%
“…Different interventions failed to change social support for PA practice among students, (Bergh et al, 2012;Lubans et al, 2012) and no robust reasons can justify our findings on the moderating role of age. One hypothesis is that, during adolescence and searching for more autonomy from their parents, students tend to start a gradual process of increasing the importance of friends' influence on their behaviors and beliefs (Cook et al, 2014). Our baseline data support this hypothesis because there are positive correlations between age and scores of support of friends (r = 0.073; P = 0.02) and negative correlations with scores of support from parents (r = − 0.071; P = 0.02, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant question is whether a feature of the target audience affects the direction and/or strength (i.e., moderator variable) of the intervention effect on PA determinants (Yildirim et al, 2011). Studies have reported that the practice and preference for PA can be different according to gender, (Perry et al, 2012;Brown et al, 2013;Salmon et al, 2009) age, (Demetriou and Höner, 2012;Cook et al, 2014) socioeconomic status (SES), (Yildirim et al, 2011;Grydeland et al, 2013) PA level, (Grydeland et al, 2013;Taymoori et al, 2008) and body mass index (BMI) status (Bergh et al, 2012;Grydeland et al, 2013). Consequently, these variables can also moderate the effect of an intervention on PA-related variables.…”
Section: Introductionmentioning
confidence: 99%
“…Such results can potentially yield recommendations for future intervention adaptation and development [ 44 ]. Previous studies on tailored PA interventions have shown that participant characteristics (such as age and gender and the intention to be sufficiently physically active) can moderate the effects of tailored PA interventions [ 45 52 ]. The short-term effects of I Move on PA at 6 months were moderated by gender, age and relational status; the effects of I Move were more pronounced in male participants, participants younger than 47, and participants who were single.…”
Section: Introductionmentioning
confidence: 99%